THE INFLUENCE OF THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY AND COMPENSATION FOR EMPLOYEE PERFORMANCE MINISTRY OF RELIGIOUS AFFAIRS DISTRICT OFFICE SERDANG BEDAGAI - Riska Dwi Ananda; Suhaila Husna Samosir; Yayuk Yuliana; Muhammad Rahmat (PT. Radja Intercontinental Publishing, 2026)
The purpose of this study is to determine and analyze the effect of the use of information technology, communication, and compensation on employee performance at the Office of the Ministry of Religious Affairs of Serdang Bedagai Regency. The type of research used is quantitative research. The population in this study were all employees of the Office of the Ministry of Religious Affairs of Serdang Bedagai Regency, totaling 64 people. Because the population is less than 100 people, the sampling technique used saturated sampling so that the entire population was used as a research sample. Data collection techniques were carried out through observation, interviews, documentation studies, and questionnaires with a Likert scale. Data analysis techniques used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests (partial), F-tests (simultaneous), and coefficients of determination with the help of the SPSS program . The results of the study indicate that the use of information technology, communication, and compensation partially each have a positive and significant effect on employee performance, as evidenced by the calculated t-value of each being greater than the t-table and a significance level of 0.000 <0.05. In addition, simultaneously all independent variables have a positive and significant effect on employee performance with an F-count value greater than the F-table and a significance value of 0.000 < 0.05. The Adjusted R Square value of 0.775 indicates that 77.5% of employee performance variation can be explained by the independent variables in this study, while 22.5% is influenced by other variables outside the study.